Dampak Pernikahan Dini di Desa Mallusesalo Dalam Tinjauan Konsep Kesetaraan Gender - Andi Bau Mallarangeng; Sulaeman; Novitasari; Andi Aulia Raodatul Husna; Nur Azlina; Baso Anugrah Hasanuddin (Compile Journal of Society Service, 2024)
The incidence of early marriages in Mallusesalo Village is rising year on year. This issue has a significant impact on the quality of children, families, family harmony, and divorce. The prevalence of early marriages in the Wajo District has increased markedly in recent years. In 2023, the rate for males was 3.16%, while for females it was 3.45%. These figures represent a significant rise from the 1,041 recorded events in the preceding year. The underlying cause is also attributable to local cultural factors, which are shaped by the social system and the tradition of early marriage that is perpetuated within families. The consequences of early marriage include children dropping out of school, the loss of their reproductive rights due to early pregnancy and childbirth, and an increased risk of low birth weight (LBW), which can lead to stunting. Despite the enactment of Law No. 16 of 2019, which establishes the minimum age for marriage at 19 years for both men and women, early marriage remains prevalent. It is therefore important to facilitate socialisation with the aim of increasing public awareness of the impact of early marriage. This will help to reduce the increasing divorce rate, problematic female reproductive health, the number of stunted children caused by teenage mothers and domestic violence.